ANALISIS PERBANDINGAN SISTEM PEMERINTAHAN INDONESIA DAN NEPAL: IMPLIKASI TERHADAP PRAKTIK ADMINISTRASI NEGARA - Deny Setyawan; Nina Fauziyah; Andini Alifa Febrianti; Nabila Aiz Azizah Putri; M.Fadly Yudha; Moh. Musleh (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2025)
The governmental system directly influences the implementation of state administration, especially when analyzing two countries with different political, social, and historical backgrounds, namely Indonesia and Nepal. The purpose of this study is to examine the differences in the structure, mechanisms, and impact of the two countries' governmental systems on political stability and public administration efficiency. The method used in this study is qualitative with a descriptive-comparative approach, where a literature review was conducted on various academic sources, constitutions, and official reports. The analysis stages include reduction, presentation, and drawing conclusions following the Miles, Huberman, and Saldana model, and validation was carried out through source triangulation. The findings of the study indicate that Indonesia, with its presidential system, can maintain political stability through direct legitimacy from the people towards the president, although it still faces internal problems such as corruption in the bureaucracy, politicization of positions, and differences in regional capabilities. On the other hand, Nepal, which uses a federal parliamentary system, experiences government instability due to weak coalitions, low bureaucratic capacity, and recurring political conflicts, despite showing progress in terms of transparency and public participation. The fundamental differences between presidential and federal parliamentary systems affect the effectiveness of public policy, the level of accountability, and the professionalism of the bureaucracy in both countries. The uniqueness of this research lies in the application of empirical analysis to the phenomenon of large demonstrations that occurred in 2025 in both countries, which clearly reflect the differences in systems in handling political crises. This study emphasizes that political stability is not always directly related to the effectiveness of public administration, and that each system of government needs to strengthen its bureaucracy, transparency, and public involvement to achieve accountable and sustainable management.